1985
DOI: 10.1079/bjn19850162
|View full text |Cite
|
Sign up to set email alerts
|

The digestion of fresh perennial ryegrass (Lolium perenneL. cv. Melle) and white clover (Trifolium repensL. cv. Blanca) by growing cattle fed indoors

Abstract: 1. Pure swards ofperennial ryegrass (Loliumperenne L. cv. Melle) or white clover (Trifolium repens L.cv. Blanca) were harvested daily at three and two stages of growth respectively, and offered to housed cattle. The grass diets comprised primary growth (May) and two later regrowths of contrasting morphology (i.e. leaf stem values of 1.54 and 2 4 4 respectively), and were characterized by high contents of water-soluble carbohydrate and neutraldetergent fibre and comparable in vitro dry matter (DM) digestibiliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0
3

Year Published

1989
1989
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 36 publications
4
30
0
3
Order By: Relevance
“…Furthermore, assuming an increased concentration of malate up to 3% of DMI, the decrease in CH 4 observed with the lucerne might also be explained by this organic acid. This effect on methanogenesis is not a characteristic of all legumes; for instance, clover (white and/or red) did not differ from ryegrass on CH 4 emissions of growing cattle (Beever et al, 1985) or dairy cows (Van Dorland et al, 2007). Several authors have shown that including tanninrich legumes (sainfoin, lotus, sulla) and shrubs in the diet contribute to a decrease in methanogenesis due to the presence of condensed tannins (see review by Waghorn, 2007) as mentioned above.…”
Section: Mitigation Through Feedingmentioning
confidence: 95%
“…Furthermore, assuming an increased concentration of malate up to 3% of DMI, the decrease in CH 4 observed with the lucerne might also be explained by this organic acid. This effect on methanogenesis is not a characteristic of all legumes; for instance, clover (white and/or red) did not differ from ryegrass on CH 4 emissions of growing cattle (Beever et al, 1985) or dairy cows (Van Dorland et al, 2007). Several authors have shown that including tanninrich legumes (sainfoin, lotus, sulla) and shrubs in the diet contribute to a decrease in methanogenesis due to the presence of condensed tannins (see review by Waghorn, 2007) as mentioned above.…”
Section: Mitigation Through Feedingmentioning
confidence: 95%
“…It is unclear from the literature whether legumes have a greater ME than grasses because metabolic studies by Beever et al (1985) and Cammell et al, (1986) have shown that the ME of perennial ryegrass was 0,34 to 1,46 MJ/kg of DM greater than that of white clover (IHfolum repens). In contrast.…”
Section: -O ^ 'mentioning
confidence: 97%
“…In addition, white clover, the dominant legume in many temperate pastures, has been found to have little impact on CH 4 emissions from cattle (Beever et al, 1985;van Dorland et al, 2007) and sheep (Lee et al, 2004;Archimè de et al, 2011;Hammond et al, 2011).…”
Section: Changing Forage Speciesmentioning
confidence: 99%